Value-relevance of Financial and Nonfinancial Information: An Empirical Study of US Motion Picture Industry - HOU, Suna (2016)
This paper examines the value-relevance of financial and nonfinancial information within the motion picture production and distribution industry. By regressing stock returns and stock prices on various combinations of reported financial variables and unreported quantitative and qualitative nonfinancial variables, it is found that both financial (earnings, book values) and nonfinancial information (release amount, user ratings) are value relevant. When combined in the same regression model, nonfinancial metrics add incremental explanatory power over that provided by conventional financial measures. The interrelation between financial and nonfinancial variables is also scrutinised to detect the sustainability-relevant factors.